Sistem Informasi Geografis Pariwisata Kabupaten Karo Menggunakan Google Maps Berbasis Web - Munthe, Henra; Pakpahan, Sorang (LPPM UNIKA Santo Thomas Medan, 2018)
Karo Regency is one of the areas in North Sumatra Province that has the potential to become a tourism area, with the Vision